Analisis Hubungan Tingkat Pendidikan Pelaku UMKM Terhadap Keberhasilan Usaha Di Wilayah Medan Timur - Feny, Feny; Danar Moreno; Salsa Nabila; Mohamad Anouvan Syumantra; Siti Suaibah Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Micro, Small, and Medium Enterprises (UMKM) are key pillars of economic growth, especially in Medan Timur. Their success is significantly influenced by the business owners' education level, which enhances managerial skills and market adaptability. However, the extent of formal education's contribution remains debated. This study analyzes the relationship between UMKM entrepreneurs' education levels and business success in Medan Timur, employing a quantitative case study approach with structured interviews. The analysis will identify correlation patterns between education and success strategies. This research aims to provide a deeper understanding of education's role in UMKM success, serving as a basis for developing effective policies and training programs to boost business competitiveness.Micro, Small, and Medium Enterprises (UMKM) are key pillars of economic growth, especially in Medan Timur. Their success is significantly influenced by the business owners' education level, which enhances managerial skills and market adaptability. However, the extent of formal education's contribution remains debated. This study analyzes the relationship between UMKM entrepreneurs' education levels and business success in Medan Timur, employing a quantitative case study approach with structured interviews. The analysis will identify correlation patterns between education and success strategies. This research aims to provide a deeper understanding of education's role in UMKM success, serving as a basis for developing effective policies and training programs to boost business competitiveness. Usaha Mikro, Kecil, dan Menengah (UMKM) adalah pilar utama pertumbuhan ekonomi, khususnya di Medan Timur. Keberhasilan UMKM sangat dipengaruhi oleh tingkat pendidikan pelaku usaha, yang meningkatkan keterampilan manajerial dan adaptasi pasar. Namun, seberapa besar kontribusi pendidikan formal masih diperdebatkan. Penelitian ini menganalisis hubungan antara tingkat pendidikan pelaku UMKM dan keberhasilan usaha di Medan Timur, menggunakan pendekatan kuantitatif studi kasus melalui wawancara terstruktur. Analisis akan mengidentifikasi pola keterkaitan antara pendidikan dan strategi keberhasilan. Diharapkan studi ini memberikan pemahaman mendalam tentang peran pendidikan dalam keberhasilan UMKM, menjadi dasar pengembangan kebijakan dan program pelatihan yang efektif untuk meningkatkan daya saing usaha.